PENGARUH KEBIJAKAN PENDANAAN DAN MODAL KERJA TERHADAP PROFITABILITAS USAHA MIKRO KECIL DAN MENENGAH DI KECAMATAN BANAWA - Wahba, Wahba (Katalogis, 2018)
This research aims to know and analyze the effects of Â financing policy and working capital simultaneously on small medium enterprise profitability in Banawa District; to know and analyze the effect of financing policy on small medium enterprise profitability in Banawa District; to know and analyze the effect of working capital on small medium enterprise profitability in Banawa District. This study involves 172 small medium enterprise entrepreneurs in Banawa District, Donggala RegencyÂ  Analysis method employed in this research is descriptive verificative using multiple linear regressions. The results show that financing policy and working capital simultaneously perform significant effect on small medium enterprise profitability in Banawa District, financing policy performs significant effect on small medium enterprise profitability in Banawa District working capital performs significant effect on small medium enterprise profitability in Banawa District